Not-so-strategic voters: Evidence from an in situ experiment during the 2017 French presidential election. (April 2022) - Baujard, Antoinette; Lebon, Isabelle
Abstract: An experiment carried out in situ during the 2017 French presidential election provides the natural conditions in which to disentangle the motivations of expressive voting and strategic voting as determinants of voters' choice. Under the two-round plurality rule, when voters vote for a single candidate in the first round, they may wish primarily to express which is their favorite candidate, or, rather, to influence the outcome of the second-round outcome by strategic voting. These two motives may coincide or conflict. We show that insincere strategic voting is relatively low in this context since it represents less than 7% of the votes cast. When the expressive and the strategic motives conflict with each other, i.e., where expression requires giving up any influence on the outcome of the election, we show that voters are twice as likely to eschew strategic voting as to vote strategically.